Fantastic and uninviting behavior: psychopathy, alcohol, and violence. Issue 3 (9th July 2018) - Swogger, Marc T.; Montry, Kathleen M.; Walsh, Zach; Kosson, David S.
Abstract : Purpose: Early clinical accounts of psychopathy suggest important relationships between alcohol use and psychopathic traits that lead to fantastic and uninviting behavior. In particular, alcohol was thought to facilitate antisocial behavior, including violence, among psychopathic individuals. The purpose of this paper is to report a review of studies that concurrently examine psychopathy and alcohol in relation to violent behavior. Design/methodology/approach: The authors searched electronic databases (PsycInfo, PUBMED) for all published studies between January 1960 and October 2016 that included the combination of alcohol and psychopathy, antisocial personality and violence, aggression. Findings: The evidence converges to indicate that, in college and community samples, self-reported antisocial lifestyle traits interact with alcohol use to predict violence beyond that accounted for by either construct. However, in correctional and clinical samples, there is no evidence that the use of alcohol increases violence for individuals high in clinically measured antisocial lifestyle traits. Originality/value: This is the first review of the empirical literature on relationships among psychopathy, alcohol, and violence. The authors provide recommendations for future research designed to fill gaps in the literature and lead to a greater understanding of the interplay among these variables.